Cysteine Duality Effect on the Corrosion Inhibition and Acceleration of 3003 Aluminium Alloy in a 2% NaCl Solution - El Ibrahimi,Brahim (2018)
Cysteine's action on 3003 aluminum alloy dissolution in a 2% NaCl solution, at different pH values, has been investigated. Weight-loss measurements, potentiodynamic polarization and electrochemical impedance at OCP were performed. The surface morphology was analyzed by SEM. The main results showed that the alloy underwent severe corrosion at 2 and 11 pH values, as compared to at 5 and 8 pH values. Furthermore, a duality effect of cysteine was noted, as it acted as a corrosion inhibitor or accelerator, depending on its concentration, and on the solution's pH value. This particular behavior can be related to the instability of the formed film adsorbed onto the metal surface. All these findings show the high complexity of cysteine action on 3003 aluminum alloy, under the investigated conditions.